Screening for cervical cancer in younger women may be an issue - A comparative study - Saha, Eti; Begum, Fouzia; Peea, Amina Jannat; Saha, Dipanwita; Halder, Dolly (Mediscope, 2020)
Cervical cancer is a burning issue in our health sector. A project on cervical & breast cancer screening has been running already in Bangladesh. All sexually active women of 30-years and above or those who are married for 10 years or more are included in this project. But significant numbers of women, less than 30 years of age were referred to Colposcopy clinic for evaluation. They also had high grade lesion. The purpose of this study was to identify the need for cervical cancer screening programme in younger women who are less than 30 years old. This is a comparative retrospective study conducted in 30 years old women and less than 30 years old (21-29 years) women, who were attending Colposcopy clinic for evaluation & treatment in Khulna Medical College & Hospital (KMCH) from January 2013 to December 2013. We analysed 235 Colposcopies in 225 women (30 years old in Group-A; less than 30 years old in Group-B) who were attending at Colposcopy clinic in Khulna Medical College Hospital in 2013. Among group A (n=90), colposcopic findings were: normal-36 (40%), CIN I-30 (33.33%), CIN II-15 (16.67%), CIN III-2 (2.22%), invasive carcinoma-3 (3.33%). Among group B (n=135), colposcopic findings were: normal-52 (38.52%), CIN I-38 (28.14%), CIN II-26 (19.25%), CIN III-3 (2.22%), invasive carcinoma-2 (1.48%). There characteristics were analysed and compared with each other. Although cervical cancer is extremely rare at younger age, there is increasing rate of younger women with high grade cervical lesion who may need treatment. It seems that these lesions have comparable behaviors as in older women. Early age of marriage is responsible for developing cervical cancer & precancerous conditions. So screening should be started in earlier. Careful colposcopic assessment and evaluation before treatment remain indispensable in this regard. Mediscope Vol. 7, No. 2: July 2020, Page 82-88